Cardiopulmonary resuscitation - Skinner, David V; Vincent, Richard (Oxford University Press, 1997)
2nd, 1997, Oxford University Press. John Radcliffe Hospital, London, U.K. . Concise guide to the management of common cardiac emergencies, particularly full cardiorespiratory arrest. For emergency room staff and paramedics.
Oxford handbooks in emergency medicine
Keywords: anesteziologie a intenzivní lékařství; kardiologie; Cardiopulmonary Resuscitation; kardiopulmonální resuscitace